Effect of Service Quality and Perceived Value Satisfaction and Loyalty Religious Tourists Visit Island Madura, Indonesia - Pribanus Wantara (AFEBI Management and Business Review, 2016)
This paper wants to examine the relationship of service quality, perceived value, satisfaction and loyalty with religious tourists who visit the island of Madura in 2015. The structural equation modeling results support the hypothesis that service quality affects directly the satisfaction and loyalty, and satisfaction directly affects loyalty, but the results do not support the hypothesis that the perceived value directly affects the satisfaction and perceived value directly affects loyalty. Quality of service only has direct and indirect influence on loyalty through satisfaction. So the stage of tourism development in Madura, quality of service is very important in building loyalty and satisfaction tourists.Keywords: Loyalty, Madura Island, Perceived Value, Satisfaction, Service Quality